2014
DOI: 10.1136/bjsports-2013-092994
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of turning and jumping and skier speed are associated with injury risk in men's World Cup alpine skiing: a comparison between the competition disciplines

Abstract: To cite: Gilgien M, Spörri J, Kröll J, et al. Br J Sports Med 2014;48:742-747.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
123
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(125 citation statements)
references
References 16 publications
2
123
0
Order By: Relevance
“…This may explain why there is a positive secular trend in body weight among elite alpine skiers (Neumayr et al, 2003;Osgnach et al, 2005;White & Johnson, 1991). However, higher mean velocities are acquired in SPEED events and the specialists in these events need to absorb higher ground reaction forces than specialists in TECH events (Gilgien, Spörri, Kröll, Crivelli, & Müller, 2014). Subsequently, SPEED specialists may need heavier and more muscular body profiles than TECH specialists to attain higher mean velocities and distribute the generated forces across the entire body.…”
Section: Discussionmentioning
confidence: 96%
“…This may explain why there is a positive secular trend in body weight among elite alpine skiers (Neumayr et al, 2003;Osgnach et al, 2005;White & Johnson, 1991). However, higher mean velocities are acquired in SPEED events and the specialists in these events need to absorb higher ground reaction forces than specialists in TECH events (Gilgien, Spörri, Kröll, Crivelli, & Müller, 2014). Subsequently, SPEED specialists may need heavier and more muscular body profiles than TECH specialists to attain higher mean velocities and distribute the generated forces across the entire body.…”
Section: Discussionmentioning
confidence: 96%
“…position, velocity and acceleration) have been proposed as reference measures representing the athlete's overall movement in space (Schiefermüller, Lindinger, Raschner, & Müller, 2004). While earlier studies mainly used three-dimensional (3D) videobased systems for the reconstruction of the CoM (Federolf, Reid, Gilgien, Haugen, & Smith, 2012;Klous, Müller, & Schwameder, 2010;Raschner et al, 2001;Reid, 2010;Reid et al, 2007;Supej, Kugovnik, & Nemec, 2004), recent approaches have suggested the use of differential global navigation satellite systems (GNSS) (Gilgien, Singer, & Rhyner, 2010;Gilgien, Spörri, Kröll, Crivelli, & Müller, 2014;Gilgien, Spörri, Limpach, Geiger, & Müller, 2014;Lachapelle, Morrison, Ong, & Cole, 2009;Supej, 2010;Supej & Holmberg, 2011;Supej et al, 2013). GNSS systems allow larger capture volumes with reasonable set-up and processing requirements.…”
Section: Introductionmentioning
confidence: 98%
“…The GNSS antenna cannot be placed at the CoM since CoM position is changing with time and satellite signals would be shaded by the skiers own body. To overcome this problem, previous researchers have placed the antenna on either the head (Brodie, Walmsley, & Page, 2008;Gilgien et al, 2013;Gilgien, Spörri, Kröll, et al, 2014;Gilgien, Spörri, Limpach, et al, 2014;Lachapelle et al, 2009; or back (Gilgien, Singer, et al, 2010;Supej, 2010;Supej & Holmberg, 2011;Supej et al, 2013). In order to overcome the problem that in neither approach was the GNSS antenna placed at the COM location, modelling methods were implemented to estimate the COM position from the antenna so that COM kinematics could be calculated (Brodie et al, 2008;Supej et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In competitive alpine skiing, skiers, on the one hand, strive to optimize their skiing by optimizing several different mechanical predictors such as time, speed, turn radius and energy dissipation [2][3][4]. Several of these parameters are, on the other hand, recognized as major risk factors for injuries in competitive skiing [5][6][7][8]. It is therefore no surprise that injury rates for competitors are very high [9].…”
Section: Introductionmentioning
confidence: 99%